2004
DOI: 10.1017/s000305540400111x
|View full text |Cite
|
Sign up to set email alerts
|

The Inefficient Use of Power: Costly Conflict with Complete Information

Abstract: R ecent work across a wide range of issues in political economy as well as in American, comparative, and international politics tries to explain the inefficient use of power-revolutions, civil wars, high levels of public debt, international conflict, and costly policy insulation-in terms of commitment problems. This paper shows that a common mechanism is at work in a number of these diverse studies. This common mechanism provides a more general formulation of a type of commitment problem that can arise in many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
134
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(138 citation statements)
references
References 18 publications
2
134
0
2
Order By: Relevance
“…Hence, the model does not speak to the inefficiency puzzle with complete information (Fearon 1995;Powell 2004). Rather, it provides a rationale for taking the military instrument seriously.…”
Section: Creating Commitments and Communicating Them Crediblymentioning
confidence: 99%
“…Hence, the model does not speak to the inefficiency puzzle with complete information (Fearon 1995;Powell 2004). Rather, it provides a rationale for taking the military instrument seriously.…”
Section: Creating Commitments and Communicating Them Crediblymentioning
confidence: 99%
“…Before moving on to empirical matters, I would like to discuss in brief how the argument presented here relates to earlier studies that have found nonlinear relationships among variables related to the 13 Faniel 2005. 14 See, for example, Fearon 1995;Powell 2004;and Acemoglu and Robinson 2006. 15 Fearon 1995, 406.…”
Section: Alternative Explanationsmentioning
confidence: 99%
“…Though the following are not models of endogenous institutions per se, Powell (2004), Egorov and Sonin (2005), and Gomes and Jehiel (2005) all construct interesting dynamic games in this spirit. Powell constructs a dynamic game in which a temporarily weak government may lack credibility to induce another government to restrain its inefficient use of power such as launching a coup or attacking.…”
Section: Summary and Review Of Literaturementioning
confidence: 99%